Retromer deficiency in amyotrophic lateral sclerosis - Perez-Torres, Eduardo J. (2020)
The retromer is a protein complex whose function is to mediate the recycling of proteins from the endosome to either the plasma membrane or the trans-Golgi network. A deficit in retromer function has been associated with multiple neurodegenerative disorders, including Alzheimer’s disease (AD) and Parkinson’s disease (PD). In both AD and PD, deficiencies have been found in retromer expression both in patient tissues and in animal models of disease. Furthermore, mutations in the retromer and in retromer-associated genes have been strongly linked with both diseases. Despite ample evidence of the link between the retromer and neurodegeneration, little is known about the retromer in the context of amyotrophic lateral sclerosis (ALS), another common neurodegenerative disorder. ALS is an adult-onset neurodegenerative disorder of the upper and lower motor neurons (MNs) characterized by muscle wasting and weakness leading to death within 3-5 years after diagnosis. To date, the most commonly used model of ALS is a transgenic (Tg) mouse that overexpresses an ALS-causing G93A mutation in the human superoxide dismutase 1 (SOD1) gene. In this study, I first establish a link between the retromer and ALS by showing that cells from ALS patients as well as tissues and cells from SOD1G93A-Tg mice express lower protein levels of the retromer core components—vacuolar protein sorting 35 (Vps35), Vps26a, and Vps29. I then establish that deficiencies in retromer core proteins have functional consequences in an in vitro model of ALS. Having found significant deficiencies in the retromer in SOD1G93A-Tg mice, I then followed the model of studies performed in mouse models of other neurodegenerative disorders by investigating whether repletion of retromer levels, either virally or pharmacologically, in SOD1G93A-Tg mice confers a therapeutic benefit. Surprisingly, I find that rather than ameliorating disease, repletion of retromer levels in SOD1G93A-Tg mice exacerbates it, resulting in a faster decline in motor performance, earlier mortality, and a decrease in MNs in the spinal cord. Finally, since retromer repletion causes deleterious effects on SOD1G93A-Tg mouse disease progression, I study the effect of a single allele deletion of Vps35 in SOD1G93A-Tg mice and find that this depletion of the retromer results in amelioration of disease, including delayed onset of symptomatology, slower decline of motor deficits, delayed mortality, and an increase in MNs in the spinal cord. Altogether, the findings reported herein, support the notion that a mild defect in retromer develops over the course of the disease, which, rather than being deleterious may be therapeutic in mutant SOD1-induced MN degeneration. Perhaps this unexpected outcome may be explained by the fact that the observed mild nature of the defect is not sufficient to kill MNs but enough to alter the trafficking of specific cargos such as AMPA receptors, allowing MNs to better withstand the neurodegenerative process.